Dragnet Girl - Hughes, Ed (BFI, 2013)
A woman persuades her gangster boyfriend to go straight and sacrifice himself to save a young student who has recently joined the gang and his sister from a life of crime. [www.bfi.org.uk]
Keywords: DVD-Video